2017
DOI: 10.3390/nu9080899
|View full text |Cite
|
Sign up to set email alerts
|

Choline Supplementation Normalizes Fetal Adiposity and Reduces Lipogenic Gene Expression in a Mouse Model of Maternal Obesity

Abstract: Maternal obesity increases fetal adiposity which may adversely affect metabolic health of the offspring. Choline regulates lipid metabolism and thus may influence adiposity. This study investigates the effect of maternal choline supplementation on fetal adiposity in a mouse model of maternal obesity. C57BL/6J mice were fed either a high-fat (HF) diet or a control (NF) diet and received either 25 mM choline supplemented (CS) or control untreated (CO) drinking water for 6 weeks before timed-mating and throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 53 publications
4
36
0
Order By: Relevance
“…However, neither HF feeding nor choline supplementation during the prenatal period alone modified blood glucose control in the postnatal life. This observation was consistent with our previous studies of fetuses exposed to the same maternal feeding model, where HFCS dams prevented fetal overgrowth in mid-gestation [4] and reduced fetal adiposity in late-gestation [5], while HF alone led to fetal overgrowth and excess adiposity, and that choline supplementation in the normal fat (control) environment had no impact on growth or adiposity. Our findings demonstrate for the first time that the metabolism-modifying effect of choline supplementation under the maternal HF condition seems to be maintained throughout the prenatal and postnatal period in male offspring.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, neither HF feeding nor choline supplementation during the prenatal period alone modified blood glucose control in the postnatal life. This observation was consistent with our previous studies of fetuses exposed to the same maternal feeding model, where HFCS dams prevented fetal overgrowth in mid-gestation [4] and reduced fetal adiposity in late-gestation [5], while HF alone led to fetal overgrowth and excess adiposity, and that choline supplementation in the normal fat (control) environment had no impact on growth or adiposity. Our findings demonstrate for the first time that the metabolism-modifying effect of choline supplementation under the maternal HF condition seems to be maintained throughout the prenatal and postnatal period in male offspring.…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned in Materials and Methods, we chose the 60% kcal fat diet since it can stably induce the obesity and GDM phenotypes in dams and offspring. In our previous studies using the same 60% kcal HF diet to examine its influence on fetal growth, we found higher fetal weight in mid-gestation and greater fetal whole-body adiposity in late gestation [4,5]. These observations suggest that the faltering in the growth of HFCO offspring likely occurred during lactation.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations